THE EFFECTIVENESS OF THE CONTEXTUAL TEACHING AND LEARNING MODEL IN IMPROVING ELEMENTARY SCHOOL STUDENTS’ SPATIAL LITERACY SKILLS - Naura Aisya Salsabila; Pupun Nuryani; Sendi Fauzi Giwangsa (Jurnal Cakrawala Pendas, 2026)
This study addresses the issue of low spatial literacy skills among elementary school students’, particularly in map-related learning. Limited students’ engagement and the lack of instructional models that support spatial literacy development are identified as contributing factors. The study aims to examine changes in students’ spatial literacy skills following the implementation of the Contextual Teaching and Learning (CTL) model. A pre experimental one-group pretest posttest design was employed involving 28 fifth-grade students’ from a public elementary school in Sukasari District, Bandung City. Data were collected using an essay based spatial literacy test and analyzed using descriptive statistics, mean difference testing, and N-Gain analysis. The findings indicate an increase in students’ spatial literacy scores from the pretest to the posttest, suggesting improved performance after the CTL-based instruction. However, due to the absence of a control group, the results should be interpreted cautiously and cannot be used to establish causal relationships. Despite this limitation, the study contributes to the growing body of literature on spatial literacy instruction by providing empirical evidence on the potential role of contextual learning strategies in supporting map-related understanding at the elementary level. Practically, the findings offer insights for Social Studies teachers on integrating contextual and experience-based approaches to enhance students’ spatial reasoning within the framework of elementary education.